Non genetic factors affecting lactation milk yield and estimation of genetic, environmental and phenotypic trends in Surti buffalo - Pawar, V; Brahmkshtri, B; Pandya, GM; Janmeda, M; Dangar, NS; Bayan, J; Tyagi, K (Indian Journal of Dairy Science, 2018)
The records of 457 Surti buffaloes covering 1346 lactations sired by 35 sires maintained at Livestock Research Station, Navsari Agricultural University, Navsari born during 1987 to 2012 were collected and analysed to examine the effect of non-genetic factors viz. season of birth, period of birth and parity on lactation milk yield. The least squares mean for lactation milk yield in Surti buffaloes was 1140.55 ± 38.33 kg. The analysis of variance revealed highly significant effects of period of birth and parity on lactation milk yield. Lactation milk yield significantly increased from 1044.77 ± 37.70 kg in 1st parity and recorded to be highest during 3rd to 7th parities (1164.98 to 1220.72 kg). Highest lactation milk yield in 5th parity and significant increase in milk yield up to 7th parity indicates potential of breed for long day yielder without any seasonal effect. Genetic trend for lactation yield was found to be positive (20.14 ± 58.23 kg) by LSMBL method and it was negative (-13.15 ± 1.89 kg) by BLUP method. The environmental trends for lactation yield were 44.37 ± 61.30 kg and 77.66 ± 19.27 kg respectively by LSMBL and BLUP methods. The phenotypic trend was also found positive (64.51 ± 19.18 kg) for lactation yield in the present study. Negative genetic trend by BLUP method stressed the need to use proven sires for attaining desired genetic improvement. Positive environmental trend indicated good managemental practises followed by the farm which also contribute to positive phenotypic trend.